2022
DOI: 10.1002/app.53492
|View full text |Cite
|
Sign up to set email alerts
|

Triazine/thiophene‐based microporous organic polymer for electrocatalytic hydrogen evolution reaction

Abstract: In this study, sulfur-enriched microporous organic polymer (MOP) was prepared using one-pot Shiff-base type polycondensation reaction of thiophendicarboxaldehyde with melamine. With 195.731 m 2 g À1 surface area and 0.047 cm 3 g À1 pore volume, the as-synthesized MOP has a cotton-like morphology and a micropore-dominated pore size distribution. After loading MOP with nickel as a co-catalyst, we demonstrated that the obtained framework could be used as an efficient and robust electrocatalyst for hydrogen evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Micro-V (cm 3 wileyonlinelibrary.com/journal/pi Generally, the mesopore volume is higher than the micropore volume, and this result is clearly evident from the gas isotherm, representing the micro-meso type. 13 Thermal stability of triazine-based polymers Thermo-oxidative stability of polymers is one of the most significant parameters concerning the usefulness of polymers in practical applications requiring air sensitivity.…”
Section: Porosity Measurements and Pore Size Distribution Of Triazine...mentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-V (cm 3 wileyonlinelibrary.com/journal/pi Generally, the mesopore volume is higher than the micropore volume, and this result is clearly evident from the gas isotherm, representing the micro-meso type. 13 Thermal stability of triazine-based polymers Thermo-oxidative stability of polymers is one of the most significant parameters concerning the usefulness of polymers in practical applications requiring air sensitivity.…”
Section: Porosity Measurements and Pore Size Distribution Of Triazine...mentioning
confidence: 99%
“…2 Triazine-conjugated and triazine-thiophene microporous polymers were applied for hydrogen production and electrocatalytic hydrogen evolution reactions. 3,4 Recently, for public health, nitrogen-rich triazine-based polymers have shown a significant performance toward capturing and storing radioactive and volatile iodine. 5 For catalytic applications, a microporous triazine-thiophene-based polymer was prepared and used as a solid acid catalyst to synthesize valuable organic compound 5-hydroxymethylfurfural from carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a singular example, Yau et al synthesized a CTF-related nickel containing microporous organic polymer incorporating triazine and thiophene moieties by polycondensation of 2,5-thiophenedicarboxaldehyde and melamine; the resulting material demonstrated an overpotential of 597 mV. 67 Among non-thiophene CTF work, Siebels et al deposited Rh- and Pt-NPs on 1,4-dicyanobenzene-based CTF-1 and the materials demonstrated overpotentials of 58 and 111 mV, respectively, in 0.5 mol L −1 H 2 SO 4 . 68 Qiao et al tested molybdenum sulfide NPs on CTF-1 achieving 93 mV.…”
Section: Introductionmentioning
confidence: 99%